Design and Evaluation of a Guided Discovery-Based Calculus Module on Derivatives with Islamic Values Integration - Suryandari, Birgita Tyas; Kim, Susan No (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop and evaluate a guided discovery-based calculus module on derivatives integrated with Islamic values to support students’ conceptual understanding, independent learning, and spiritual awareness in higher education mathematics learning. Methodology: This study employed a Research and Development (R&D) method using the 4D model (define, design, develop, disseminate). Data were collected through questionnaires, validation sheets, and documentation. Instruments included expert validation sheets and student response questionnaires. Data were analyzed using descriptive quantitative and qualitative techniques with a Likert scale (1–4). Main Findings: Results show that the module achieved valid criteria across material, media, and Islamic values aspects after revision. Material validation increased to 3.75, media design to 3.8, and Islamic values to 4.0. Limited trial results indicated an average score of 3.56, categorized as very attractive. These findings confirm that the module is feasible and well-received by students. Novelty/Originality of this study: This study presents an integrative calculus module combining guided discovery learning with Islamic values on derivative topics. It simultaneously addresses cognitive and spiritual aspects within a single instructional design. This approach provides a holistic learning resource and contributes to advancing mathematics education by integrating pedagogical strategy and value-based learning.